Anaerobic digestion of pre-treated fruit and vegetable wastes - Ho, Jia Jia. (2011)
The aim of this project is to examine biogas production (i.e. methane yield) from anaerobic digestion of thermally pre-treated fruit and vegetable wastes (FVW). This is done via Biochemical Methane Potential (BMP) batch experiments with 3gVS/l loaded input of wastes. FVW were thermally pre-treated at two different temperatures (i.e. 120⁰C and 100⁰C) for 30 minutes. For comparative purpose, raw FVW (i.e. not thermally pre-treated) were used as control. In addition, the raw FVW and thermally pre-treated FVW were separated into two batches where one batch includes pH adjustment during anaerobic digestion and the other exclude pH adjustments. The pH was adjusted to optimum pH for anaerobic digestion (i.e. pH 7.0).